Parents and Caregivers Satisfaction After Palliative Treatment of Spastic Hip Dislocation in Cerebral Palsy - Koch, Aleksander; Krasny, Joanna; Dziurda, Magdalena; Ratajczyk, Magdalena; Jozwiak, Marek (Frontiers in Neurology, 2021)
Objectives: Pain appearance is one the most common complication of spastic hip disease in children with cerebral palsy (CP). It determines child and caregiver quality of life and life priorities. Reconstruction hip surgery should be considered as a treatment of choice. Some clinical conditions give the inability to perform such a procedure. In our paper, we would like to present four palliative methods of spastic hip dislocation treatment in children with CP. Material: We analyzed four groups of patients treated because of hip pain. Inclusion criteria were pain appearance (visual analog scale-11 or numeric rating scale-11) and hip joint dislocation (migration percentage >80%). All patients were admitted to our department between 2008 and 2018. In the first group, patients were treated only by steroid injections to hip joints; in the second group, patients were recruits after hip interposition arthroplasty with shoulder spacer; in the third group, they were patients after valgus subtrochanteric osteotomy (Schanz); and in the fourth group, these were patients after proximal femoral resection (Castle procedure). The minimal follow-up time was 2 years. The first group consisted of 15 patients (15 hips) with a mean age of 15.5 (8–17) years; the second group, 20 patients (24 hips) with a mean age of 14.2 (9–22.6) years; the third group, 22 patients (24 hips) with a mean age of 13.5 (7–20.5) years; and the fourth group, 10 patients (15 hips) with a mean age of 12.9 (7–17.6) years. Methods: Radiological evaluation was based on a standardized anteroposterior X-ray of the hip joints. Pain severity before surgery and at the last follow-up time was measured by visual analog scale-11. Parents or caregivers were asked about their child's pain during sitting, perineal care, and rest. During the visit, all caregivers were asked about treatment satisfaction (no 0 to max 10) and if they would decide again for the same surgery. Results: In all groups of patients, we observed a decrease in pain complaints. The observed reduction of pain in the first group was from 7.88 (4–10) to 3.08 (0–8) (p = 0.05), but results of injection were observed only for 4 months (2–8), and it has to be repeated (average: two times). In the second group, level of pain was reduced from 4.93 (1–10) to 0.93 (0–5) (p < 0.001); in the third group, from 6.22 (3–10) to 0.59 (0–6) (p < 0.001); and in the fourth group, pain reduces from 5.43 (2–10) to 2.13 (0–5) (p < 0.001). Observed changes concerned mostly sitting position and perineal care. The complication rate was in the second group, 6 of 24 cases of extraarticular ossification; in the third group, 2 of 24 cases with extraarticular ossification, two cases of revision surgery. In the fourth group, two cases needed another femoral resection. In the first group, five patients died during follow-up time, so they were excluded from the study. In the steroid injection group, parents' treatment evaluation was 6.83 (0–10), and only in three cases that they would resign from the treatment. In the hip interposition arthroplasty group, caregivers' evaluation was 7.41 (0–10), and in five cases, parents did not accept the surgery. In the Schanz osteotomy group, parents' evaluation was 5.9 (0–10), and in eight cases, caregivers would not repeat surgery. In the proximal femoral resection group, satisfaction was the highest, 8.3 (3–10), and only two parents would not decide for surgery again. Conclusion: All procedures can be considered as palliative treatment options for pain complain in a spastic hip joint dislocation in children with CP. Steroid injections to the hip joint need to be repeated, and with the follow-up time, it becomes less effective. Steroid injection seems to be the treatment of choice for patients with general anesthesia contraindications. Interposition arthroplasty of the hip joint seems to give better final results, but the highest parents' satisfaction surprisingly was observed in the proximal femoral resection group, but differences were not statistically significant.